Variation in monthly sizes of home‐ranges of Hooded Vultures Necrosyrtes monachus in western, eastern and southern Africa. (23rd April 2020) - Thompson, Lindy J.; Barber, David R.; Bechard, Marc J.; Botha, André J.; Wolter, Kerri; Neser, Walter; Buechley, Evan R.; Reading, Richard; Garbett, Rebecca A.; Hancock, Pete; Maude, Glyn; Virani, Munir Z.; et al.
Abstract : Tracking studies are often used to inform conservation plans and actions. However, species have frequently only been tracked in one or a few localities, whereas space use can be remarkably flexible, especially in long‐lived species with advanced learning abilities. We assessed variability in space use in the Critically Endangered Hooded Vulture Necrosyrtes monachus by pooling movement data from three populations across the species' sub‐Saharan range (in South Africa, Botswana, Ethiopia, Kenya, The Gambia and Mozambique). We estimated minimum convex polygons and kernel density estimators (KDEs) and compared monthly home‐range sizes between breeding and non‐breeding seasons, age‐classes and subspecies, accounting for uneven sampling within groups. Mean (± sd) monthly home‐range sizes (95% KDEs) for adult Hooded Vultures from southern (12 453 ± 21 188 km 2, n  = 82) and eastern Africa (3735 ± 3652 km 2, n  = 24) were 103 and 31 times larger than those of conspecifics from western Africa (121 ± 98 km 2, n  = 48). This may relate partly to subspecific differences, and individuals with small home‐ranges in western Africa and Ethiopia were trapped in urban environments. Regional variation in space use by Hooded Vultures may be linked to flexibility in feeding behaviour (degree of commensalism) which may arise in response to resource availability and persecution in different areas. Age‐class also affected monthly home‐range sizes, with immature birds generally having larger monthly home‐range size estimates than adults. Our results highlight the flexibility of Hooded Vultures in terms of their home‐range sizes and suggest that home‐range sizes differ between populations and individuals, depending on the extent of human commensalism. Our results also reaffirm the importance of international co‐operation in conservation efforts aimed at protecting this wide‐ranging, non‐migratory species.